Surgical Approaches to Gene and Stem Cell Therapy for Retinal Disease - Stout, J. Timothy (Mary Ann Liebert, Inc., 2011)
Gene and cell therapy holds tremendous promise for treating a variety of acquired and inherited disorders of the retina that impact on vision. Much has been written about the impact of vectors in delivering genes to cells of the retina in vivo. A critically important component of these kinds of therapies is the procedure used to introduce the cells or vectors. Drs. Stout and Francis provide a broad overview of gene and cell therapies for diseases of the retina, focusing on the procedures that could be used for delivery.